2019
DOI: 10.1177/0022243719849940
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Rapid Delivery in Omnichannel Retailing

Abstract: The authors study how faster delivery in the online channel affects sales within and across channels in omnichannel retailing. The authors leverage a quasi-experiment involving the opening of a new distribution center by a U.S. apparel retailer, which resulted in unannounced faster deliveries to western U.S. states through its online channel. Using a difference-in-differences approach, the authors show that online store sales increased, on average, by 1.45% per business-day reduction in delivery time, from a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(79 citation statements)
references
References 33 publications
(33 reference statements)
2
77
0
Order By: Relevance
“…Along these lines, the majority of studies relied on data from multiple industries (Alexander & Cano, 2019; Buldeo Rai et al., 2019b; Jocevski et al., 2019; Larke et al., 2018; Saghiri et al., 2017; Valentini et al., 2020; Yrjölä et al., 2018a). Some sector‐specific studies employed data from the fashion (Jo et al., 2020; Juaneda‐Ayensa et al., 2016; Sebald & Jacob, 2020; Silva et al., 2020; Wollenburg et al., 2018a; Ye et al., 2018) and apparel sectors (Aw, 2019; Fisher et al., 2019; Frasquet et al., 2019; Rodríguez‐Torrico et al., 2017; Rosenmayer et al., 2018). The vast majority of studies were conducted in developed economies, leaving other geographic areas and markets largely unexplored.…”
Section: Synthesis Of Findings and Future Research Agendamentioning
confidence: 99%
“…Along these lines, the majority of studies relied on data from multiple industries (Alexander & Cano, 2019; Buldeo Rai et al., 2019b; Jocevski et al., 2019; Larke et al., 2018; Saghiri et al., 2017; Valentini et al., 2020; Yrjölä et al., 2018a). Some sector‐specific studies employed data from the fashion (Jo et al., 2020; Juaneda‐Ayensa et al., 2016; Sebald & Jacob, 2020; Silva et al., 2020; Wollenburg et al., 2018a; Ye et al., 2018) and apparel sectors (Aw, 2019; Fisher et al., 2019; Frasquet et al., 2019; Rodríguez‐Torrico et al., 2017; Rosenmayer et al., 2018). The vast majority of studies were conducted in developed economies, leaving other geographic areas and markets largely unexplored.…”
Section: Synthesis Of Findings and Future Research Agendamentioning
confidence: 99%
“…Specifically examining the issue of delivery, Fisher, Gallino, and Xu (2019) used quasi-experimental data to show that faster delivery of online orders increased sales in both online and offline channels of an apparel retailer. They showed that each business-day reduction in delivery period increased online sales of the apparel retailer by about 1.45 percent and offline sales by about 0.61 percent.…”
Section: Determinants Of Store and Channel Choice Behaviormentioning
confidence: 99%
“… Wang and Goldfarb (2017) Customer-level purchase data & Poisson regression Opening an offline store increased online sales of the retailer in areas with no prior brand presence but decreased online sales in areas with existing brand presence. Fisher et al (2019) Quasi-experimental design Faster delivery of online orders increased sales in both online and offline channels of an apparel retailer. This study Survey data & Multivariate probit model When opening online stores, offline retailers should provide larger assortment, competitive prices, and purchase convenience instead of relying unduly on quicker delivery to compete against online retailers.…”
Section: Determinants Of Store and Channel Choice Behaviormentioning
confidence: 99%
“…The literature has a long history of studying logistics services (Peng & Lu, 2017). In online retailing contexts, extant literature has suggested that delivery performance is a potent predictor of consumer satisfaction (Koufteros, Droge, Heim, Massad, & Vickery, 2014; Thirumalai & Sinha, 2005), loyalty (Heim & Field, 2007), behavior intention (Boyer & Hult, 2006), referral (Griffis, Rao, Goldsby, Voorhees, & Iyengar, 2012), product return (Rao, Rabinovich, & Raju, 2014), and repurchase (Fisher, Gallino, & Xu, in press; Rao, Griffis, & Goldsby, 2011). Most prior studies have highlighted the importance of logistics services for online retailers using survey methods.…”
Section: Introductionmentioning
confidence: 99%
“…Using archival data from an online retailer of printed material, Rao et al (2011) identify the negative impact of failure to deliver within a promised time limit. Fisher et al (in press) demonstrate a meaningful revenue impact from delivery speed improvement for an online apparel retailer with a single brand.…”
Section: Introductionmentioning
confidence: 99%